2017
DOI: 10.1039/c6cp08495h
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the trans axial ligand of cobalt corroles on water oxidation activity in neutral aqueous solutions

Abstract: A series of cobalt complexes of 5,10,15-tris(pentafluorophenyl)-corrole [Co(tpfc)] (1) with various axial ligands were synthesized and examined as single-site catalysts for water oxidation. The used axial ligands include 4-cyanopyridine (py-CN), pyridine (py), 4-(dimethylamino)pyridine (py-NMe), 4-methoxypyridine (py-OMe), 1-methylimidazole (im-Me), and thiophenolate (thi). Complexes 1-py and 1-py-OMe were structurally characterized. The Co ion in both structures has an almost identical distorted octahedral co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 69 publications
2
63
0
Order By: Relevance
“…[96] In addition, the influence of axial ligands was also reported for Co corroles comprising different axial N-donors ( Figure 9). [97] The highest catalytic activityw itha no nset potential of 530 mV vs. NHE was obtainedf or complex 14 possessing the ligand with highest electron-donating properties. Along this line, complex 16 shows the lowest activity with an onset potentialo f5 80 mV vs. NHE.…”
Section: Functional Homogeneous Systems For Oermentioning
confidence: 98%
“…[96] In addition, the influence of axial ligands was also reported for Co corroles comprising different axial N-donors ( Figure 9). [97] The highest catalytic activityw itha no nset potential of 530 mV vs. NHE was obtainedf or complex 14 possessing the ligand with highest electron-donating properties. Along this line, complex 16 shows the lowest activity with an onset potentialo f5 80 mV vs. NHE.…”
Section: Functional Homogeneous Systems For Oermentioning
confidence: 98%
“…[1][2][3][4][5] During the past few decades, extraordinary efforts have been dedicated to the synthesis of manganese-based molecular complexes to mimic the structure and function of the OEC. [6][7][8][9][10] Other transition metals were also used for the synthesis of water oxidation catalysts, including Ru, [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Ir, [25,26] Fe, [27][28][29][30][31] Co, [32][33][34] Ni, [35][36][37] and Cu. [38][39][40] Recently,the Llobet group disclosed the synthesisofaheterotrinuclear Ru 2 Mn complex A 0 {[Ru II (tpy)] 2 (m-[Mn II (bpp) 2 ]) (OAc) 2 } 2 + [tpy = 2,2':6',2''-terpyridine, bpp = 3,5-bis(2-pyridyl)pyrazolate].…”
Section: Introductionmentioning
confidence: 99%
“…ChemSusChem 2019, 12,3209 -3235 www.chemsuschem.org 2019 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim macrocycle with fluorobenzene and this modified cobalt corrole (CoH bF CXÀCO 2 H) was stable during the OER. [154] They synthesized [Co(tpfc)] complexes with different axial ligands and found that [Co(tpfc)],w ith an electrondonating trans-axial ligand,e xhibited high activity owing to the trans effect. [151] It was revealed that the fluorobenzene might be away to improvethe electrophilicity of MÀO( Mi sm etal), which would contribute to nucleophilic attack by water.C hen and co-workersf urthers tudied OÀOb ond formation on CoH bF CX-CO 2 Ht hrough DFT calculations.…”
Section: Mononuclear Cobalt-based Catalystsmentioning
confidence: 99%
“…In 2017, Cao and co-workerss tudied the influence of the trans-axial ligand on the catalytic activity of [Co(tpfc)]. [154] They synthesized [Co(tpfc)] complexes with different axial ligands and found that [Co(tpfc)],w ith an electrondonating trans-axial ligand,e xhibited high activity owing to the trans effect. With regard to the ligand,C ao and co-workers found that the Co-corrolew ith base pendant L CH 2 POĂ°OHÞ 2 ÀCo showedh igher OER activity than that with acid pendants, thus indicating that the CH 2 PO(OH) 2 group, as an intramolecular base, contributedt oO ÀOb ond formation for the OER.…”
Section: Mononuclear Cobalt-based Catalystsmentioning
confidence: 99%